PENGARUH IMPLEMENTASI PEMBELAJARAN PENDIDIKAN PANCASILA BERBASIS KURIKULUM MERDEKA TERHADAP KEDISIPLINAN SISWA DALAM MENAATI TATA TERTIB SEKOLAH DI SMP TRI JAYA MEDAN - Jesika Yolanda, Putri; Habeahan, Sampitmo; El Muhtaj, Majda; Dharma, Surya; Jamaludin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to test the significance of the influence of the implementation of Pancasila Education learning based on the Independent Curriculum on student discipline in obeying the rules at Tri Jaya Medan Middle School. Using a quantitative correlational approach with an Ex-Post Facto explanatory design, this study included the entire active population through a total sampling technique of 98 students. Primary data collection was executed through a Likert-scale questionnaire instrument (28 valid and reliable items; α> 0.800), supported by triangulation of field observation methods and documentation extraction. The results of the statistical prerequisite test confirmed that the distribution of residual data was normally distributed (Asymp. Sig. Kolmogorov-Smirnov 0.897> 0.05) and had a linear line projection (Sig. Deviation from Linearity 0.362> 0.05). Simple linear regression analysis produced a deterministic formulation Y = 10.245 + 0.784X. Partial hypothesis testing (t-test) convincingly rejects and accepts , as evidenced by the calculated t_ratio (8.790) exceeding the t_table (1.984) at an absolute significance level of 0.000 < 0.05. The recorded coefficient of determination () value of 0.446 indicates that the pedagogical quality intervention provides a causal contribution of 44.6% to fluctuations in student discipline compliance, while the residual margin of 55.4% is explained by external sociological determinants beyond the model's scope. This study concludes that the adoption of participatory methods such as Project Citizen and the optimization of educators' role models have successfully reconstructed the student paradigm; changing obedience based on coercive fear into an autonomous constitutional awareness that values ​​the protection of Human Rights (HAM).This study aims to test the significance of the influence of the implementation of Pancasila Education learning based on the Independent Curriculum on student discipline in obeying the rules at Tri Jaya Medan Middle School. Using a quantitative correlational approach with an Ex-Post Facto explanatory design, this study included the entire active population through a total sampling technique of 98 students. Primary data collection was executed through a Likert-scale questionnaire instrument (28 valid and reliable items; α> 0.800), supported by triangulation of field observation methods and documentation extraction. The results of the statistical prerequisite test confirmed that the distribution of residual data was normally distributed (Asymp. Sig. Kolmogorov-Smirnov 0.897> 0.05) and had a linear line projection (Sig. Deviation from Linearity 0.362> 0.05). Simple linear regression analysis produced a deterministic formulation Y = 10.245 + 0.784X. Partial hypothesis testing (t-test) convincingly rejects and accepts , as evidenced by the calculated t_ratio (8.790) exceeding the t_table (1.984) at an absolute significance level of 0.000 < 0.05. The recorded coefficient of determination () value of 0.446 indicates that the pedagogical quality intervention provides a causal contribution of 44.6% to fluctuations in student discipline compliance, while the residual margin of 55.4% is explained by external sociological determinants beyond the model's scope. This study concludes that the adoption of participatory methods such as Project Citizen and the optimization of educators' role models have successfully reconstructed the student paradigm; changing obedience based on coercive fear into an autonomous constitutional awareness that values ​​the protection of Human Rights (HAM).